A comparative study on long term electrical performance of right ventricular outflow tract pacing versus right venticular apical pacing in patients with permanent pacemakers in Hospital Universiti Sains Malaysia - Ab. Rahim, Siti Mariam (2010)
Background: Since the introduction of the transvenous cardiac pacing almost five decades ago, the right ventricular apical (RVA) has been the preferred site for ventricular lead attachment. This is due to the ease of placement, stability and reliability. However, from experimental and clinical studies showed that prolonged pacing from the RVA has been shown to be associated with progressive left ventricular dysfunction as demonstrated by heart failure, atrial fibrillation and increased in morbidity and mortality. This led to an interest in alternative RV pacing sites particularly the right ventricular outflow tract (RVOT). It is theoretically associated with more physiological ventricular activation comparing with the conventional pacing site. However there is lack of data on procedural success and long term electrical performance that limits the adoption of RVOT septum pacing as an alternative site to RV apical pacing. The primary aim of the study is to investigate the long term safety of ventricular lead performance and changes in pacing parameters of RVOT pacing comparing with the conventional RVA pacing. From previous study, long term was referred to more than 6 months. Methods: A total of 96 patients underwent permanent pacemaker implantation at Hospital Universiti Sains Malaysia from January 2002 until June 2008. Out of this number, only 66 patients had complete data. They were enrolled and collected data were analyzed retrospectively. The position of endocardial leads were confirmed by a retrospective analysis of the radiographic appearance. The patients were divided into two group based on the pacing site. One group of patients with RV A pacing and another group of patients with RVOT pacing. Data on stimulation threshold, R wave sensing and lead impedance at time of pacemaker implantation and two years post implantation were collected and analyzed. Patients' demographic, symptoms at presentation and indications for pacing also been analyzed. Results: Pacing thresholds, impedance values, and R wave amplitudes measured at implantation and 2 years post-implantation did not significantly differ between RVOT and R VA pacing except for the final lead impedance and threshold. The impedance of the RVOT lead was significantly higher than RVA site. The threshold of the RVOT lead was significantly better than RVA. However values for both parameters were within the accepted range. There was no lead dislodgement or any other procedural related complications during follow up. Conclusion: The ventricular lead performance of right ventricular outflow tract pacing site is safe and better compared with the right ventricular group. The pacing parameters are comparable with conventional RVA pacing in the long term.